Privately-directed participatory planning: Examining Toronto’s Quayside smart city - Nelischer, Kate (Canadian Planning and Policy / Aménagement et politique au Canada, 2024)
The second wave of smart cities emerged in response to criticism of the top-down methods used to manage early smart cities, and promised a new, ‘citizen-centric’ approach. To understand the application of this approach in the smart city planning process there is a need for further empirical research. This paper offers a case study of the participatory planning process used in Quayside, a smart city planning effort in Toronto (Canada). Through semi-structured interviews (N=35), participant observation, and document analysis, this research finds that although Quayside included a lengthy engagement program, citizen influence was limited. This is a result of a lack of participation in initial project visioning, and the direction of the subsequent citizen engagement process by a private technology company, enabled through a public-private partnership. Based on these findings, I argue that a smart city planning process cannot be citizen-centric if citizens are unable to determine project goals. I also suggest that privately-directed engagement processes can amplify the power discrepancies that are well studied within government-directed processes and introduce new accountability challenges.